Investigating the Role of Physical Activity and Exercise in Preventing Obesity and Type 2 Diabetes: A Mixed-Methods Approach - Shah, Syed Abdal Hussain; Khan, Haris Riaz; Afghan, Tahira Sher; Ahmed, Noman; Saeed, Anas; Ullah, Muhammad Najeeb; Iftikhar, Nayyab; Gul, Beena; Bibi, Misbah (Indus Journal of Bioscience Research, 2025)
Objective: This review aims to synthesize recent research on the impact of exercise and physical activity in preventing T2DM and obesity, using a mixed-methods approach. Methods: A thorough literature review was conducted, incorporating findings from 59 recent studies. The review combined quantitative data on physiological mechanisms, exercise modalities, and intensities, with qualitative insights into behavioral and psychological factors influencing exercise adherence. Results: The review elucidates how exercise enhances metabolic health through improved insulin sensitivity, glucose metabolism, and fat reduction. Different forms and intensities of physical activity were shown to have varied effects on metabolic health, with both aerobic and resistance exercises contributing to overall benefits. Qualitative research highlighted individuals' attitudes, motivations, and barriers to maintaining regular physical activity. Factors such as personal goals, social support, and psychological barriers were identified as critical determinants of exercise adherence. Discussion: The findings emphasize the need for targeted interventions and policies to promote regular physical activity. Strategies should address both physiological benefits and behavioral challenges, incorporating personalized approaches to enhance adherence and efficacy. Conclusion: Regular exercise plays a crucial role in reducing Type 2 Diabetes Mellitus (T2DM) and obesity while improving metabolic health. A mixed-methods approach combining physiological and qualitative research enhances understanding of these interactions. Exercise promotes glucose absorption by translocating GLUT4 to the cell surface and increases insulin sensitivity in skeletal muscles. It reduces hepatic glucose production, enhances mitochondrial biogenesis, and improves oxidative capacity. Additionally, exercise stimulates lipolysis, lowers triglycerides and LDL cholesterol, and increases HDL cholesterol. It also reduces chronic inflammation by modulating cytokines and adipokines, ultimately improving insulin sensitivity and overall metabolic function, making it essential for diabetes management.